Determinan Akuntabilitas Kinerja Instansi Pemerintah Daerah Di Masa Pandemi Covid-19 (Studi Empiris Daerah Istimewa Yogyakarta) - Fidela Nuzul Azmi; Rizal Yaya; Tumirin Tumirin (Jurnal Manajerial, 2023)
Background – Covid-19 Pandemic has caused changes in budget allocation and declining in local government revenue which may affect its accountability performance. Aim – The purpose of this study is to empirically test whether during covid-19 pandemic the clarity of budget targets, accounting controls, reporting systems, and human resources can improve the performance accountability of government agencies in the Special Region of Yogyakarta (DIY). Design / methodology / approach – ). This research uses survey questionnaire. The sample in this study were 89 respondents consisting of the Head of Regional Apparatus Organization (OPD), Treasurer of OPD, and Secretary of OPD. The data collection technique in this study used questionnaire with purposive sampling technique. The data analysis technique is based on statistical multiple linier regression. Findings – Based on the variables tested in order to obtain significance, the results obtained were 2 of them had significance while the other 2 had no significance. Conclusion - The variables of clarity of budget targets and quality of human resources had a significant and positive effect on government agency performance accountability during the COVID-19 pandemic, while accounting control and reporting system variables had no significant and positive effect on government agency performance accountability. Research implication – This research implies that local governments need to ensure clarity of budget targets and the quality of human resources in order to improve their accountability performance especially during crisis. Limitations – This study is limited to the Special Region of Yogyakarta. For greater validity, future study needs to extend the research scope to national area.